MENGELOLA SAMPAH PLASTIK DENGAN MENINGKATKAN KESADARAN MASYARAKAT TERHADAP PERILAKU DAUR ULANG - Muhammad Lukman Baihaqi Alfakihuddin; Azalia Putri Budi; Dina Kartika; Silvira Trijayati (Jurnal Inovasi Pendidikan dan Sains, 2022)
Many sea and land animals have died as a result of plastic waste, which has contributed to climate change. Plastic has the characteristic of being hard to decompose and hazardous to burn. There are many efforts being made to reduce the impact of plastic waste on the environment because of this problem. Plastic waste awareness has been raised as part of these efforts. While there is existing research regarding the topic, detailed information regarding plastic waste in Jakarta seems to be lackluster, especially considering the ineffectiveness of the government ban on plastic usage without proper education for the people. This study used a quantitative survey as a form of quantitative research. According to the results of the study, attitudes, behavioral control, moral norms, and intentions are significant factors that influence recycling behavior. This research will benefit the people in Semarang, as they will have a cleaner environment. Also, the reduction of plastic waste would benefit the world's climate and ecosystem, benefiting the Indonesian people and humanity in general.